PURIFICATION OF RIBOSOME-INACTIVATING PROTEIN (RIP) OF MIRABILIS JALAPA L. LEAVES BY CM-SEPHAROSE CL-6B AND SEPHACRYL S-300HR COLUMN - Sudjadi .; Sismindari .; Tenti Herawati; Alberta Tri Prasetyowati (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2003)
Total protein of Mirabilis jalapa leaves has activities to cleave supercoiled DNA to nick circular and linear and to cleave glycosidic bound of adenin4324 of yeast 26S rRNA. The protein was cytotoxic on HeLa and Raji celllines through apoptosis and necrosis mechanisms, respectively. However, the protein, poseess the activities, has yet been resolved. Therefore, protein furification to obtain single protein is necessary. Crude extract of M.jalapa leaves was prepared using 5 mM sodium phosphate buffer pH 7,2 containing 0,14 M sodium chloride. Total protein was obtained by precipitating the extract at 100% saturated ammonium sulfate and then dialyzed against phosphate buffer. The protein was purified by CM-Sepharose CL-6B, a cation exchange column. After loading the protein, the column was washed with 5 mM sodium phosphate buffer pH 6,5. The proteins were then eluted with linear gradient of increasing sodium chloride concentration. The fraction with supercoiled DNA-cutting activity was performed for N-glycosidase activity. The active fraction was a subject for further purification with Sephacryl S-300HR, a gel filtration column. The purity and size protein were confirmed by SDS-polyacrylamide gel electrophoresis with silver nitrate staining. RIP like protein was eluted from CM-Sepharose CL-6B on 0,25 – 0,3 M sodium chloride. The size of protein is around 30 kD.Key words : RIP purification, M.jalapa leaves, CM-Sepharose CL-6B, Sephacryl S-300HR